Mycobacterium chelonae hand infection following acupuncture: a case report and literature review - Matic, Sladjana; Teodosic, Valerija; Zagorac, Slavisa (Frontiers in Medicine, 2024)
Hand infection caused by atypical mycobacteria is an uncommon condition. We present a case of hand infection caused by Mycobacterium chelonae in a patient who had undergone acupuncture. The clinical features, treatment, and outcome are described. Biopsy and cultures are essential for the diagnosis because Mycobacterium chelonae is a rare cause of human infection and is difficult to diagnose unless suspected. The patient was successfully treated through a combination of surgical excision, debridement, and antimicrobial therapy. We also reviewed the available literature to summarize the experience related to this infectious entity.